The influence of lubricating coolant and processing modes on surface roughness during face milling of workpieces made of aluminum alloys - A. G. Kisel; D. S. Makashin (Омский научный вестник)
Within the framework of these studies, experimental studies are carried out on the effect of using coolants of various types — synthetic «BIOSIL-S», semi-synthetic «SP3» and water-based «Smalta-4» — on the roughness of the machined surface of an aluminum billet during milling. The roughness of the machined surface is evaluated by the Ra parameter using a MarSurf PS1 portable profilometer. As a result of the research, it is found that coolants affect the quality of the resulting surface in different ways. The best surface quality is obtained at a cutting speed of V=283 m/min and a feed of S=0,02 mm/tooth using a BIOSIL-S coolant, which is due to rational cutting conditions and the physical properties of the coolant.